Undergraduate Students' Perspective on Self-Directed Learning in Speaking Skill - Yulianti, Rida; Miftakh, Fauzi; Fitriyana, Wahyudin (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2021)
This study aims to describe undergraduate students' perspectives on the implementation of self-directed learning in improving speaking skills. The participants of this research are 8th semester students at Universitas Singaperbangsa Karawang with the amount of 30 students. This study employed descriptive method, where the data gained through semi-structured interview and questionnaires. The findings indicated that all participants agreed that self-directed learning is an effective method that is used outside the classroom. They also agreed that self-directed learning can help them achieve their learning goals and get used to being more active and responsible in their learning process. In addition, in carrying out self-directed learning activities, most of the participants prefer to use audio-visual media. Furthermore, this study suggests teachers to provide a foothold to students about the importance of self-management in the learning process towards self-directed learning so that students are more independent and can achieve the learning objectives.